Effectiveness of the modified Lafontaine criteria in predicting loss of reduction in distal radius fracture (Annals of Medical Research, 2024)
Aim: This study aimed to retrospectively test the ability of the modified Lafontaine criteria to predict loss of reduction in distal radius fractures treated conservatively.Materials and Methods: Between January 2019 and July 2021, a total of 171 patients aged 50-60 years diagnosed with distal radius fractures and treated with closed reduction and short arm casting were evaluated radiologically. Patients were categorized into two groups based on the modified Lafontaine criteria: Group 1 included patients meeting fewer than three criteria, while Group 2 included those meeting three or more criteria. Parameters such as age, gender, fracture side, fracture type (according to AO classification), follow-up period, radial length, and volar tilt degree after initial reduction were compared with their respective values at the last follow-up. Additionally, changes between values obtained at the last follow-up and those after initial reduction were analyzed.Results: According to the modified Lafontaine criteria, 68 patients were classified into Group 1 and 103 patients into Group 2. Both groups exhibited similar distributions in terms of age, fracture side, and follow-up period (p>0.05). However, Group 2 showed a significantly higher proportion of females compared to Group 1 (p=0.004). Furthermore, Group 2 differed significantly from Group 1 in terms of fracture distribution (p=0.024). Radial lengths and volar tilt degrees after initial reduction showed no significant differences between the groups (p>0.05). At the last follow-up, it was observed that changes in radial length, volar tilt degree, and reduction loss were significantly greater in Group 2 (p
Keywords: Distal radius fractures; Effectiveness; Modified lafontaine criteria; Loss of reduction